Pacing and sprint performance in speed skating during a competitive season - Muehlbauer, T.; Schindler, C.; Panzer, S. (International Journal of Sports Physiology and Performance, 2010)
Purpose: This study assessed the effect of time spent in several race sectors (S) on finishing time and determined the variance in distribution of skating time and in total race time for official 1000-m sprint races conducted during a competitive season. Methods: Total race and sector times for the first 200 m (S1) and the following two 400-m laps (S2 and S3) of 34 female and 31 male elite speed skaters performed during a series of World Cup Meetings were analyzed. Results: Overall, skaters started fast, reached their peak in S2, and slowed down in S3, irrespective of race category considered (eg, rank of athlete, number of race, altitude of rink, starting lane). Regression analyses revealed that spending a shorter fraction of time in the last (women in S3: B = 239.1; P < .0001; men in S3: B = 201.5; P < .0001) but not in the first (women in S1: B = -313.1; P < .0001; men in S1: B = -345.6; P < .0001) race sector is associated with a short total race time. Upper- compared with lower-ranked skaters varied less in competition-to-competition sector and total race times (women: 0.02 to 0.33 vs 0.02 to 0.51; men: 0.01 to 0.15 vs 0.02 to 0.57). Conclusion: This study confirmed that skaters adopted a fast start pacing strategy during official 1000-m sprint races. However, analyses indicate that shortening time in the closing but not in the starting sector is beneficial for finishing fast. In addition, findings suggest that lower-ranked skaters should concentrate training on lowering their competition-to-competition variability in sector times.